Lethal intimate partner violence and gendered dimensions of the COVID-19 lockdown in Nigeria: evidence from a descriptive analysis of secondary data - Vitalis U Ukoji; Vitus N Ukoji (BMJ Public Health)
Introduction Concerns emerged over the escalation of intimate partner violence (IPV) as many governments imposed COVID-19 lockdown measures. This paper examined the lethality trends, gender contexts and sources of fatal IPV during the prelockdown, lockdown and postlockdown years (2019–2021) in Nigeria. This research aims to shed light on the impact of the pandemic lockdown on IPV-related mortalities.Methods The study used secondary data from the Nigeria Watch database, an online resource on lethal violence and human security in Nigeria. It relied on IPV datasets extracted and analysed descriptively at the univariate level.Results Results indicate a steady increase in IPV-related mortalities, with 205 fatalities—62 in 2019, 69 in 2020 and 74 in 2021—resulting from 180 IPV incidents. Males were the main protagonists, as the majority of IPV victims were women, including female spouses (51%) and female lovers (23%), compared with male spouses (18%) and male lovers (7%). A trend analysis of IPV-related fatalities showed that the worst affected states are in southern Nigeria, with Lagos recording the most cases. Apart from the undefined causes of IPV-related fatalities, more deaths emanated from arguments between intimate partners (50) and infidelity (37). Aside from other reasons, most victims died from dangerous weapons (46) and battering (27).Conclusion This paper underscores the steady increase in IPV-related deaths year over year, not just during the COVID-19 lockdown period, and highlights the importance of policy and practise to prevent and respond to IPV incidents.